Analisis Implementasi Kurikulum Merdeka Di Sd Negeri Kalanganyar - Tutut Putri Ramadani; Rudy Handoko (Journal of Research and Development on Public Policy, 2024)
This research aims to analyze how the Merdeka Curriculum is implemented at the Kalanganayar State Elementary School, with a focus on the learning process and outcomes carried out by educators. The research method used is a qualitative approach using data collection techniques through observation, interviews and document analysis. The research results show that the implementation of the Independent Curriculum at Kalanganayar State Elementary School faces a number of challenges, including limited resources, the need for training for teachers, and efforts to integrate the curriculum with the local context. However, the research also found significant achievements, such as increased student engagement in learning, development of skills relevant to the 21st century, and increased learning motivation.